PRODUÇÃO, COMPOSIÇÃO E QUALIDADE OXIDATIVA DO LEITE DE OVELHAS SUPLEMENTADAS COM ERVA-MATE - évelyn Silva de Melo Soares (2022)
The first article addresses the hypothesis that the association of soybeans in grain and yerba mate can increase the concentration of polyunsaturated fatty acids (PUFA) with less oxidation of milk from lactating ewes reared in tropical pastures. Sixteen sheep were randomly distributed in a 2x2 factorial scheme. Four different diets were elaborated: control (without soybeans in grain or yerba mate); soybean in grain (210 g/kg of DM); yerba mate (110 g/kg of DM) and a combination of soybeans and yerba mate. The ingestion of yerba mate has reduced the consumption of DM, etheric extract (EE), protein, lactose, degreased dry extract, density, omega - 3 concentrations and the ratio of saturated/monounsaturated fatty acids (FA), but increased the concentration of monounsaturated FA and the sequestering power of free radicals by DPPH without altering the concentrations of conjugated dienes and the concentrations of substances reactive to thiobarbituric acid in milk. Supplementation with soybean grain decreased the lambs' birth weight; on the contrary, it increased the concentrations of conjugated linoleic acid (CLA), PUFA, omega - 6, the omega ratio - 6/omega - 3 and the total blood cholesterol. Thus, it is concluded that the addition of yerba mate did not influence the oxidative profile of milk. While supplementation with soybean grain improved the milk FA profile, increasing CLA and PUFA concentrations. The association of soybean grain and yerba mate helps to improve the fat quality of milk from sheep raised in tropical pastures, as shown by the enhanced antioxidant activity, although it does not help prevent the oxidation of milk rich in PUFA. The second article compared the different extraction methods for total lipids and evaluated the effect of these methodologies on the quantitative composition of fatty acids in milk from lactating ewes raised on tropical pastures. The methodologies used were simple direct transesterification, using the HPLC grade organic solvent n-hexane, Bligh; Dyer (cold extraction, extracting mixture proportions 5, 10 and 15 mL in a ratio of 2:1: 1 (v / v / v) of chloroform-methanol-water). The fatty acid methyl esters were separated by gas chromatography coupled with a flame ionization detector (GC-FID). The results show that there was no significant difference (p<0.05) in the total lipid content between the extraction methods. However, Bligh's method; Dyer obtained the best yield of lipids to be extracted from 's milk, since the volume with 15 mL of the extraction solution was able to identify 87% of the chromatographic peaks. It was also observed that ewe's milk has a higher percentage of palmitic, stearic and oleic fatty acids, with percentages of 20.1%, 15.5% and 33.1%, respectively. Therefore, the extraction mixture with a volume of 15 mL used in this study can be an alternative to perform the extraction of milk fat from lactating ewes raised in tropical pastures as a routine method, as it expresses the best lipid content of this food.